Urgensi Kedudukan Wali dalam Pernikahan - Mustakim, Ahmad; Arham, Muhammad (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
This study aims to address issues regarding the significance of a guardian (wali) in marriage. A marriage guardian is the person entitled to marry off a woman to a man of her choice. The wali acts on behalf of the bride in the marriage contract (akad nikah). Both the guardian and witnesses are responsible for ensuring the validity of a marriage contract. The purpose of this research is to educate the public about the importance of the wali's presence in marriage so that people do not easily disregard the role of the wali due to certain circumstances. The findings of this study reveal that the role of a wali is crucial in a marriage, as the wali is a fundamental pillar determining the validity of the marriage. Therefore, the position of the wali requires special attention, especially in conducting a marriage ceremony. The urgency of the wali's role is also emphasized in the Qur'an, Hadith, as well as in Indonesian laws, including the Compilation of Islamic Law and the Marriage Law.